ROH HIZBUT TAHRIR DI BUMI PANCASILA - Arthur Aritonang (The Way Jurnal Teologi dan Kependidikan, 2020)
This article examines the HTI organization whose ambition is to realize the caliphate system in Pancasila land. The existence of HTI is ideologically and practically very destructive of the spirit of the identity of the Indonesian nation as a state with schemes. The existence of the HTI organization raises concerns for the future of a pluralistic Indonesian nation. During the Reformation era, HT / Hizbut Tahrir's activities turned into an organization that received legal legitimacy from the Government so that the Hizbut Tahrir Indonesia organization was formed. The purpose of this article is to capture how the history of HT development reached Indonesia? What is the government's attitude towards HTI organizations in Indonesia? How did the "spirit" of HTI followers carry out their propagandistic actions after the HTI organization was dissolved by the government. For this reason, the method used in this research is a qualitative method (literature) which focuses on the topic of the Hizbut Tahrir movement in Indonesia. As a conclusion in this study are (1) The ideology of the caliphate brought by M. Mustofa (Indonesia) and Abdurrahman al-Baghdadi (Lebanon) who are members of HT based in Jordan then spread the ideology of the caliphate in Indonesia, (2) President Jokowi in 2017 officially disbanded HTI organizations, (3) Lectures containing anti-government and Pancasila narratives built by HTI preachers in mosques, utilizing democratic facilities and freedom of expression in public spaces to socialize caliphate discourse by taking cover behind preaching.